Differences in muscle quality, muscle strength, and functional motor performance between people after stroke and age- and sex-matched apparently healthy adults: a cross-sectional study - Domínguez-Sanz, Natalia; Trandafir, Paula Camelia; Bays-Moneo, Ana Beatriz; Insausti Serrano, Ana María; Ramírez-Vélez, Robinson (Frontiers in Neurology, 2025)
IntroductionAfter stroke, muscle quality deteriorates due to neuromuscular impairments, disuse, and ageing-related changes. While prior studies have examined global muscle alterations, less is known about regional differences in muscle quality across specific limb compartments, and how these differences relate to strength and functional performance. Understanding whether anterior and posterior compartments of the upper and lower limbs are differentially affected may help target rehabilitation strategies.MethodsThis cross-sectional study investigated regional differences in muscle quality between people after stroke and age- and sex-matched apparently healthy adults, focusing on the anterior and posterior compartments of the upper and lower limbs. Muscle quality was assessed using ultrasound-derived muscle thickness (MT) and echo intensity (EI), alongside motor function (Modified Ashworth Scale), muscle strength (handgrip, knee flexion, and extension), and anthropometric measures. Analyses of covariance, adjusted for age, sex, body mass index, Mini Nutritional Assessment score, and Mini-Mental State Examination score, were conducted to compare the less affected and affected sides in people after stroke with apparently healthy controls. In total, 102 participants were assessed: people after stroke (n = 49) and apparently healthy controls (n = 53).ResultsPeople after stroke exhibited significantly higher EI values in the biceps brachii (BB), rectus femoris (RF), tibialis anterior (TA), and gastrocnemius (GS) on both the affected and contralateral side (p < 0.05). MT values of the BB (p < 0.001), TA (p < 0.001), and GS (p < 0.001) on the affected side were significantly lower than those in controls. EI values of the BB and RF were negatively correlated with handgrip and knee extension strength, respectively, while MT of these muscles showed strong positive associations with strength outcomes (p < 0.001). Similar trends were observed for knee flexion.DiscussionDistinct regional patterns of muscle quality loss were observed in people after stroke, with lower MT and higher EI values correlating with reduced strength. These findings highlight the importance of assessing both structural and functional parameters across limb regions to better understand muscle deterioration and guide targeted interventions in ageing and post-stroke populations.